1972
DOI: 10.1021/ic50111a030
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity in octahedral complexes. XIII. Trans-to-cis isomerizations and hydrolysis reactions of some chromium(III) anionic complexes

Abstract: The kinetics of isomerization and hydrolysis reactions of some anionic complexes of chromium(III) have been investigated.The results obtained for the trans-to-cis isomerizations of Cr(ox)2(OH2)2~, Cr(ox)2(OH2)OH2-, and Cr(ox)2(OH)23are interpreted in terms of one-ended dissociation of the oxalato ligand. In contrast, the similar malonato series reveals a breakdown in the kinetic pattern, which suggests a change in mechanism for the aquohydroxo and diaquo forms involving the primary dissociation of a water mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…Since there were two ligands being replaced by two water molecules, it was assumed that consecutive reactions were occurring (eq 2 and 3). It can be k¡ dJ-Cr(C204)2(HC0N(CH3)2)2" + H20 -*m-Cr(C204)2(HC0N(CH3)2)(0H2)" +HCON(CH3)2 (2) cis-Cr(C204)2(HC0N(CH3)2)(0H2)" + H20 m-Cr(C204)2(0H2)2" + HCON(CH3)2 (3) shown that for a system of this type that follows pseudofirst-order kinetics eq 4 is valid.1 A is the absorbance at time A -A" = axe~k'1 + a2e'klt (4) t and A" is the absorbance at infinite time (10 half-lives). The constants ax and a2 are defined by eq 5 and 6, where l is the graphically for kx and k2.x The results as well as the leastsquares calculated values of the activation parameters are in Table I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there were two ligands being replaced by two water molecules, it was assumed that consecutive reactions were occurring (eq 2 and 3). It can be k¡ dJ-Cr(C204)2(HC0N(CH3)2)2" + H20 -*m-Cr(C204)2(HC0N(CH3)2)(0H2)" +HCON(CH3)2 (2) cis-Cr(C204)2(HC0N(CH3)2)(0H2)" + H20 m-Cr(C204)2(0H2)2" + HCON(CH3)2 (3) shown that for a system of this type that follows pseudofirst-order kinetics eq 4 is valid.1 A is the absorbance at time A -A" = axe~k'1 + a2e'klt (4) t and A" is the absorbance at infinite time (10 half-lives). The constants ax and a2 are defined by eq 5 and 6, where l is the graphically for kx and k2.x The results as well as the leastsquares calculated values of the activation parameters are in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…The anation reactions of Co(III), Rh(III), and Cr(III) pentaammine complexes have been extensively studied for a wide range of organic and inorganic entering ligands in aqueous medium.4"21 During the anation process, the ammonia ligands are tightly bound to the metal ion22 and, in most cases,20 are substitution inert. These reactions are generally accepted5 to proceed according to an interchange mechanism:7•23 M(NH3)5OH23+ + X" |M(NH3)50H23+,X1 (1) {M(NH3)5OH23+,X"j M(NH3)5x2+ + h2o (2) where M = Co(III), Rh(III), or Cr(III) and X = Cl, Br, NCS, CH3COO, etc. Burnett18 suggested that ion triplets also participate in the above mechanism at high concentrations of X", although this suggestion was criticized in later work.24…”
Section: Introductionmentioning
confidence: 99%
“…Krishnamuthy [1] has reviewed the substitution reactions of the oxalate complexes of chromium(III). However, very few papers have been published on the kinetics of Cr(C 2 O 4 ) 2 X 2 nmoiety; where X is any monodentate ligand other than water [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The substitution reactions of the oxalato complexes of chromium(III) have been reviewed by Krishnamurthy [1]. However, very few papers have been published on the kinetics of Cr(C 2 O 4 ) 2 X 2 nmoiety; where X is any monodentate ligand other than water [2][3][4][5][6]. Amino acids are organic molecules that constitute a most important part of biological structure and body chemistry.…”
Section: Introductionmentioning
confidence: 99%